Mass Media, Communication, and Culture - Magarati, Shyam Lal (Surkhet Journal, 2014)
This article deals with the definition of the mass media, mass media and communication, categories of communication, kinds of mass communication tools, advantage and disadvantage of mass communication. Similarly it deals about the media, communication and culture and the conclusion. It includes the traditional, as well as new media, newsworthiness and role of the media agencies, media personalities and the media pundits. The article’s main focus is the role of media in the cultural context and need of media in present time to change and develop the society in reality.